A Novel Approach to Left Ventricular Filling Pressure Assessment: The Role of Hemodynamic Forces Analysis - Airale, Lorenzo; Vallelonga, Fabrizio; Forni, Tommaso; Leone, Dario; Magnino, Corrado; Avenatti, Eleonora; Iannaccone, Andrea; Astarita, Anna; Mingrone, Giulia; Cesareo, Marco; Giordana, Carlo; Omedè, Pierluigi; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: diastolic function in patients with heart failure (HF) is usually impaired, resulting in increased left ventricular (LV) filling pressures, whose gold standard assessment is right heart catheterization (RHC). Hemodynamic forces (HDFs) analysis is a novel echocardiographic tool, providing an original approach to cardiac function assessment through the speckle-tracking technology. The aim of our study was to evaluate the use of HDFs, both alone and included in a new predictive model, as a potential novel diagnostic tool of the diastolic function. Methods: HDFs analysis was retrospectively performed in 67 patients enrolled in the “Right1 study”. All patients underwent RHC and echocardiography up to 2 hours apart. Increased LV filling pressure (ILFP) was defined as pulmonary capillary wedge pressure (PCWP)≥15mmHg. Results: 33 patients out of 67 (49.2%) showed ILFP at RHC. Diastolic longitudinal force (DLF) was associated with the presence of ILFP (OR=0.84 [0.70;0.99], p=0.046). The PCWP prediction score we built including DLF, ejection fraction, left atrial enlargement and e’ septal showed an AUC of 0.83 [0.76-0.89], with an optimal internal validation. When applied to our population, the score showed a sensitivity of 72.7% and a specificity of 85.3%, which became 66.7% and 94.4% respectively, when applied to patients classified with “indeterminate diastolic function” according to current recommendations. Conclusion: HDFs analysis could be an additional useful tool in diastolic function assessment. A scoring system including HDFs might improve echocardiographic accuracy in estimating LV filling pressures. Further carefully designed studies could be useful to clarify the additional value of this new technology.